2013
DOI: 10.1007/s11060-013-1209-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFRvIII mutant DNA in the peripheral blood of brain tumor patients

Abstract: Glioblastoma multiforme (GBM) is the most aggressive brain tumor in adults and remains incurable despite multimodal intensive treatment regimens including surgical resection, radiation and chemotherapy. EGFRvIII is a truncated extracellular mutant of the EGF receptor (EGFR) found in about a third of GBMs. It confers enhanced tumorigenic behavior and is associated with chemo- and radio-resistance. GBM patients testing positive for EGFRvIII have a bleaker prognosis than those who do not. Targeting EGFRvIII posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…EGFRvIII can be detected in the peripheral blood of brain tumor patients, opening the possibility of screening patients for anti-EGFRvIII therapies and monitoring response. 41 Several studies suggest the potential of EGFR as a prognostic factor in GBM given the presence of a specific EGFRvIII mutational variant with a clear role in gliomagenesis, 29 while others have not shown a clinical correlation between EGFR and survival. 16 In one study, EGFR amplification resulted in significantly lower OS than did EGFR wild type (13.3 vs 26.6 months); 29 however, a study of long-term survivors of GBM (> 36 months) showed that alterations in EGFR were not significant predictors.…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…EGFRvIII can be detected in the peripheral blood of brain tumor patients, opening the possibility of screening patients for anti-EGFRvIII therapies and monitoring response. 41 Several studies suggest the potential of EGFR as a prognostic factor in GBM given the presence of a specific EGFRvIII mutational variant with a clear role in gliomagenesis, 29 while others have not shown a clinical correlation between EGFR and survival. 16 In one study, EGFR amplification resulted in significantly lower OS than did EGFR wild type (13.3 vs 26.6 months); 29 however, a study of long-term survivors of GBM (> 36 months) showed that alterations in EGFR were not significant predictors.…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…To test whether suPAR is increased in plasma from patients with EGFRvIII-positive GBMs, we obtained plasma samples and applied a PCR assay to detect circulating DNA derived from full-length WT-EGFR and EGFRvIII (47). We used previously described primers (41), which flank the deletion region in EGFRvIII, to specifically detect DNA from this EGFR variant.…”
Section: Soluble Upar Generation By Gbm Cells In Vivo-to Test Whethermentioning
confidence: 99%
“…About 10-60% of the patients with GBM have EGFRvIII which can be detected in the peripheral blood of brain tumors. The detection of this mutation in brain cancer patients has great importance for anti-EGFRvIII therapies and patients can be monitored to track their response to these therapies [11,12]. Better and deeper knowledge of mechanistic insights that cause EGFR heterogeneity in GBM will prove to be helpful in identification of drugs with maximum efficacy.…”
Section: Proliferative and Antiproliferative Pathways And Their Rolesmentioning
confidence: 99%